Physics Learning Media with Multirepresentation: A Systematic Literature Review - Latifah, Riska Nurul; Sutopo, Sutopo; Hidayat, Arif (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
This research examines the development of physics learning media with a multi-representation approach through a systematic literature review. The research method follows the PRISMA stages with data sources from Google Scholar, including articles published between 2015-2023, which SINTA/Scopus index. Of the initial 769 titles, 30 articles were selected based on inclusion and exclusion criteria. The results show the dominance of development research focused on high school students and validated by experts. Modules are the most frequently used media. A spike in publications occurred in 2020, possibly due to the COVID-19 pandemic, which encouraged innovation in distance learning. Research finds that interactive media encourages active student involvement more effectively in increasing understanding of complex physics concepts. The multiple representation approach is proven to improve students' understanding, because it allows them to access information through multiple representations. Further research is needed on a variety of physics topics and involving more diverse samples and the use of new technologies. This article provides practical recommendations for developers and educators to discover trends, challenges, and opportunities in the further development of multi-representation-based physics learning media.